The Importance Of Human Resources Training To Improve Organizational Performance - Tini Mogea (Lembaga Pengembangan Kinerja Dosen, 2023)
In an organization or company, human resources cannot be separated from training activities. Training for human resources is a necessity for every organization or institution because almost everyone recognizes that the success of an organization or company is highly dependent on the human resources that manage them. Therefore, training is needed by employees so that they can improve their abilities, knowledge skills, motivation, and behavior. In today's modern era of development, human resource training is very important, because the formal education that employees have undergone is not enough to meet the demands of jobs and positions in organizations and companies. In addition, placing human resources directly at work does not guarantee that they will understand their duties and responsibilities well. New human resources often feel less confident and feel they do not understand their roles and responsibilities in the organization or company where they work. Therefore, new employees should receive training in the form of training that leads to an introduction to corporate culture and values, regulations, and policies, as well as their main tasks, which support the achievement of the vision and mission of the organization or company. Human resources who lack self-confidence are unlikely to carry out their duties and obligations to the fullest, especially in educational institutions. In addition, human resources professionals who have worked in organizations and companies for a long time also need to receive training to improve their skills, insights, and motivation in supporting the achievement of the organization's vision and mission.